Effect of Cross Gender Identity on Recognition Memory and Purchase Intention of Gender Congruent Versus Gender Neutral Products - Lalwani, Anushka (My University, 2024)
The present study investigates the effect of cross gender identity on consumer memory and purchase intention for gender congruent-incongruent versus gender neutral products. The deep encoding hypothesis is a theory that suggests that when we learn and remember information, it is processed and encoded at multiple levels of depth. This depth of processing can affect the strength and longevity of the memory .This experiment was designed in E-prime .The participant was called in the laboratory and made to sit comfortably. After obtaining informed consent, the participants were briefed on the task which was divided into two sessions: a practice session and an experimental session. The presentation duration for stimuli in the practice session mirrored that of the experimental session. The stimuli covered eight distinct product categories such as perfume, wallet, face cream, shoes, clothes, watch, sunglasses and shampoo. Following each advertisement in the practice stage, participants responded to a product inquiry display where participants had to report the content of the advertisement indicating immediate memory. The practice session concluded with a 20-second break, followed by the commencement of the experimental session, during which written instructions were provided. In the experimental session, participants were exposed to a total of 30 advertisements one at a time, (including 10 gender stereotype-congruent, 10 gender stereotype-incongruent, and 10 neutral advertisements). Notably, 15 advertisements from the training stage were reintroduced, alongside 15 newly designed advertisements. Following the presentation of each advertisement, participants indicated whether they recognized the advertisement from the training stage by pressing "Y" for yes or "N" for no indicating “recognition memory”. After this, participants were asked to mention their purchase intention for the advertisement on a 7-point rating scale. The inquiry was framed as follows: "After viewing the 9 advertisement, to what extent would you consider choosing the product?" Participants responded on a scale from 1 to 7, where 1 denoted "strongly disagree" and 7 signified "strongly agree." After the experiment the Participants were also asked to fill Blanchard and Blanchard cross gender identity Questionnaire .One hundred and twenty individuals participated in the study.To determine the outcomes for the collected data, descriptive statistics, the T test, and ANOVA were computed.The results showed that there was significant interaction between the product type and Cross gender Identity.
Keywords: Cross-gender identity; Schema congruence; Deep Encoding Hypothesis; Gender neutral products; Consumer decision making